(untitled) (Journal of Applied Oral Science, 2011)
The evaluation of oral and vocal fold diadochokinesis (DDK) in individuals with voice disorders may contribute to the understanding of factors that affect the balanced vocal production. Scientific studies that make use of this assessment tool support the knowledge advance of this area, reflecting the development of more appropriate therapeutic planning. Objective: To compare the results of oral and vocal fold DDK in dysphonic women and in women without vocal disorders. Material and methods: For this study, 28 voice recordings of women from 19 to 54 years old, diagnosed with dysphonia and submitted to a voice assessment from speech pathologist and otorhinolaryngologist, were used. The control group included 30 nondysphonic women evaluated in prior research from normal adults. The analysis parameters like number and duration of emissions, as well as the regularity of the repetition of syllables "pa", "ta", "ka" and the vowels "a" and "i," were provided by the Advanced Motor Speech Profile program (MSP) Model-5141, version-2.5.2 (KayPentax). The DDK sequence "pataka" was analyzed quantitatively through the Sound Forge 7.0 program, as well as manually with the audio-visual help of sound waves. Average values of oral and vocal fold DDK dysphonic and nondysphonic women were compared using the "t Student" test and were considered significant when p